Video Assisted Thoracoscopy Surgery (VATS) as Minimal Invasive Approach for Thymoma with Myasthenia Gravis in Gatot Soebroto Central Army Hospital: A Case Report - Febyan; Joni Indah Sari; Sri Handawati Wijaya; Andreas Andri Lensoen (PT Kalbe Farma Tbk., 2018)
Mediastinal thymoma is rare, although it is the most common anterior mediastinal mass. It tends to grow slowly and benign, but still potentially malignant. Surgery is the mainstay of treatment. The procedure of choice is still standard or partial sternotomy thymomectomy. Video Assisted Thoracoscopic Surgery (VATS) to mediastinal and lung tumor has shown promising result. The potential advantages of this approach compared to sternotomy include better cosmetic, less postoperative pain, shorter length of stay, earlier return to daily activities, less bleeding and fewer other complication. Timoma adalah jenis tumor mediastinum yang langka, banyak ditemukan di mediastinum anterior. Timoma berkembang lambat dan bersifat jinak, namun dapat menjadi ganas. Pembedahan merupakan penatalaksanaan utama, prosedur timektomi atau sternotomi parsial masih banyak digunakan. Bedah toraks dibantu video/video assisted thoracoscopy (VATS) telah menunjukkan hasil sangat baik untuk tumor mediastinum dan tumor paru. Keunggulan teknik VATS dibandingkan dengan teknik sternotomi, dari segi kosmetik lebih baik, nyeri pasca-operasi lebih sedikit, masa perawatan lebih singkat, lebih cepat kembali ke aktivitas sehari-hari, pendarahan dan komplikasi lainnya minimal.